Comparison of pharmacokinetics and the exposure–response relationship of dapagliflozin between adolescent/young adult and adult patients with type 1 diabetes mellitus. Issue 8 (20th June 2019) - Busse, David; Tang, Weifeng; Scheerer, Markus; Danne, Thomas; Biester, Torben; Sokolov, Viktor; Boulton, David; Parkinson, Joanna
Abstract : Aims: To quantitatively compare pharmacokinetics (PK) and the exposure–response (ER) relationship of the sodium‐glucose cotransporter‐2 inhibitor, dapagliflozin, between adolescents/young adults and adults with type 1 diabetes mellitus (T1DM). Methods: Data from 2 clinical studies for dapagliflozin were analysed using a non‐linear mixed‐effects approach. The PK and the relationship between dapagliflozin exposure and response (24‐hour urinary glucose excretion) were characterized. PK was evaluated using a 2‐compartment model with first‐order absorption while the exposure response‐relationship was analysed using a sigmoidal maximal‐effect model. The 24‐hour median blood glucose, estimated glomerular filtration rate (eGFR), sex, age and body weight were evaluated as covariates. Results: A 2‐compartment model with first order absorption provided a reasonable fit to the dapagliflozin PK data. Body weight was found to be a significant covariate on dapagliflozin exposure. The ER relationship was best described by a sigmoidal maximal effect model with 24‐hour median blood glucose and eGFR as significant covariates on maximal effect. In accordance with the observed data, model‐predicted urinary glucose excretion response following 10 mg dapagliflozin dose was higher in the study in adolescents/young adults (138.0 g/24 h) compared to adults (70.5 g/24 h) with T1DM. This is linked to higher eGFR and 24‐hour median blood glucose in this trial. Conclusions: Dapagliflozin PK and ER relationship were similar in the 2 analysed studies after accounting for covariate effects. These results suggest that no dose adjustment is required for adolescent patients with T1DM.